WAYS OF IMPROVING THE FULLNESS OF LOCAL BUDGETS AS A COMPONENT OF LOCAL GOVERNMENT BODIES FINANCIAL BASE - HROMOVA, O.; ABDULLAIEVA, A.; SHEVCHUK, A. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The issue of improving filling local budgets  process has been examined in the article as a component of the local governments financial base in order to obtain the most efficient budget and make the most effective decisions by local budgets. The issue of local budgets is especially relevant on the way of Ukraine's European integration. The local budgets creating largely depends on the rightness, completeness and optimality of the provisions of the Budget Code application. In addition, local budgets have become more stable and predictable as the number of non-profit responsibilities has been reduced. The economic and social development of any country depends to a large extent on the development of its territories. This, in its turn, requires appropriate financial support, which is implemented through the local budgets formation. Increasing the importance of local budgets in the implementation of social and economic regulation is a significant factor during  the further development of the country. The urgency of the problem of generating local budget revenues and using their funds has increased in the context of the fiscal and economic crisis. Ensuring local self-government with stable and sufficient financial resources is the key to establishing effective and efficient local government. Moreover, without the financial independence of local budgets with numerous components and taking into consideration the tax potential of each territory, the construction and development of an efficient social economy is impossible.
Keywords: local budgets; taxes and fees; tax revenues; non-tax revenues; personal income tax; income base